SCIENTIFIC BASIS AND PRACTICAL RESULTS OF THE "BRANDBOOK" CONCEPT FOR FRANCHISING BRANDS (Marketing Journal, 2025)
The article analyzes the scientific and theoretical foundations of the “brand book” concept for brands operating within the franchising system, as well as its role and practical significance in marketing communications. The study examines the concepts of “brand identification,” “corporate design,” and “visual identity system” in relation to standardization mechanisms in franchising business models. The results indicate that the brand book serves as an essential strategic tool for establishing a unified corp orate culture within a franchise network, building consumer trust, and increasing marketing efficiency.
Keywords: franchising; brand book; brand identification; corporate design; visual communication; marketing strategy. № 10-SON OKTA BR; 2025 -YIL 400